Struktur Geologi Bawah Permukaan Cekungan Bintuni Berdasarkan Data Gaya Berat - Handyarso, Accep; Padmawidjaja, Tatang (Jurnal Geologi dan Sumberdaya Mineral, 2017)
Bintuni Basin is one of the giant basins in Eastern Region of Indonesia (KTI). Until now there are only few oil and gas production fields in the Bintuni Basin. This case prompted the government to accelerate the discoveries of new oil and gas reserves in Eastern Region of Indonesia, particularly in the Bintuni Basin. Gravity method is one of geophysical method that is commonly used in preliminary studies of sedimentary basins. Bouguer anomaly obtained is reduced by using an average density based on the Nettleton method. Regional–residual anomaly separation is performed based on the spectral analysis. Residual anomaly showed anticline closures with a northwest–southeast directions, and also there are indication of some strike–slip faults which are expected as the result of the compression due to the Pacific Oceanic Plate and the Australian Continent Plate movement. The result from spectral analysis showed that the average depth of the bedrock is up to 6.5 km. Based on the 2.5D subsurface geological structures estimation indicates shallowing basement toward Mogoi and Kamundan district area with some fault structures that allows migration of the hydrocarbon from Pratertier source rocks to the Kais reservoir. Keywords: Bintuni Basin, Bouguer, Residual, SpectralAnalysis, Anticline